2012
DOI: 10.1037/h0100941
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analytic Psychotherapy (FAP): A review of publications from 1990 to 2010.

Abstract: Functional Analytic Psychotherapy (FAP), a therapy based on radical behaviorism, establishes the priority of the therapeutic interaction as a mechanism of change in psychotherapy. Since the first book on FAP appeared in 1991, it has been the focus of many papers and has been incorporated by the community of behavior therapists. This paper is a review of 80 international publications on FAP from 1990 to 2010, including publications from Brazil, the United States, Spain, Switzerland and Colombia. The goal was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 56 publications
0
16
0
10
Order By: Relevance
“…Research has shown that FAP might be effective for the treatment of depression, personality disorders, anxiety disorders, chronic pain and interpersonal problems, with growing empirical support for other conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that FAP might be effective for the treatment of depression, personality disorders, anxiety disorders, chronic pain and interpersonal problems, with growing empirical support for other conditions [22].…”
Section: Introductionmentioning
confidence: 99%
“…To the extent that the activities can be used within the FAP framework to evoke CRB2s that are naturally reinforced by the therapist and generalized to clients' daily lives, these tools can improve the intensity and power of psychotherapy. When considering these exercises, it is important to note that while a growing body of empirical evidence indicates FAP as a package is effective in treating a wide variety of mental health and intimacy related issues (Mangabeira, Kanter, & Del Prette, 2012; Kanter, Tsai, Holman, Koerner, 2013), there is no research assessing the efficacy of each of these evocative activities. As such, while future research specifically should address which activities have measurable positive effects on client problems, defined individually for each client, our extensive clinical experience suggests that these structured, evocative activities can be creatively adapted to individual clients to facilitate meaningful change.…”
Section: Resultsmentioning
confidence: 99%
“…A Psicoterapia Analítica Funcional, apesar de apresentar baixo controle experimental nos seus poucos dados sobre TEPT (Mangabeira, Kanter & Del Prette, 2012), seria uma alternativa para essas lacunas já que é baseada na análise do comportamento (evidências encontradas por Bisson & Andrew, 2007), apresenta como intervenção o foco nas relações interpessoais, por meio da relação terapêutica, e por ser uma terapia de terceira onda, com foco na função do comportamento emitido, sendo específica e única para cada indivíduo (fator que pode ser significativo para administrar a intervenção e diminuir a evasão de terapia). Ademais, os pressupostos e a interação lógica da FAP apresentam diversos dos possíveis determinantes de eficácia para o tratamento do TEPT (Wampold et.…”
Section: Psicoterapia Analítica Funcional E O Transtorno De Estresse unclassified